KONSEP TAUHID DALAM KEHIDUPAN UMAT ISLAM - Amina Mina; Nur Fajar; M. Amin (STKIP Subang, 2025)
This article discusses the concept of tawhid as the fundamental foundation of Islamic teachings and its implications for the personal and moral development of Muslims. The problem addressed in this study is the decline in moral awareness caused by a weak understanding of tawhid. The purpose of this article is to explain the meaning, types, and urgency of tawhid in shaping Islamic personality and ethics. This research uses a qualitative descriptive method with a literature review approach, analyzing books, journal articles, and relevant scientific publications. The results show that tawhid, which includes rububiyah, uluhiyah, and asma wa sifat, plays a crucial role in guiding human behavior, strengthening moral values, and creating spiritual awareness in daily life. Therefore, a correct and comprehensive understanding of tawhid is essential for building morally upright and spiritually strong Muslim individuals.